استكشاف المعارف في الويب الدلالي (استرجاع المعلومات من قواعد المعرفة) - باسل الخطيب; كامل جعفر (Tishreen University, 2016)
يُعتبر الويب الدلالي ثورة جديدة في عالم الويب، حيث تصبح المعلومات والبيانات قابلة للمعالجة منطقياً من قِبل برامج الحاسوب، بحيث تتحول تلك المعلومات والبيانات إلى شبكة معارف ذات معنى مُحدّد. يُشكّل الويب الدلالي مستقبل الويب الحالي مع الإشارة إلى أن البحوث والدراسات العربية مازالت قليلة نسبياً في هذا المجال. نعرض في هذه الورقة دراسة مرجعية عن الويب الدلالي والطرق المختلفة لاستكشاف المعارف واستنباط المعلومات المفيدة من الكم الهائل من البيانات التي يوفرها الويب. كما نُقدّم مثال برمجي قمنا بتطويره كتطبيق لبعض التقانات التي يُقدمها الويب الدلالي ولاسيما طرق استكشاف المعارف فيه. نوفر في هذا المثال البرمجي المبسط بعض الخدمات المتعلقة بالتعليم العالي الحكومي السوري، مثل معلومات عن الجامعات الحكومية السورية كاسم الجامعة (الافتراضية، دمشق، تشرين، حلب والبعث)، موقع الجامعة، عنوان موقعها على شبكة الويب، عدد الطلاب فيها، وملخص عن الجامعة، مما يُساعد العملاء الأذكياء على إيجاد تلك الخدمات ديناميكيا. Semantic Web is a new revolution in the world of the Web, where information and data become viable for logical processing by computer programs. Where they are transformed into meaningful data network. Although Semantic Web is considered the future of World Wide Web, the Arabic research and studies are still relatively rare in this field. Therefore, this paper gives a reference study of Semantic Web and the different methods to explore the knowledge and discover useful information from the vast amount of data provided by the web. It gives a programming example like application of some of these techniques provided by the Semantic Web and methods to discover the knowledge of it. This simplified programming example provides services related to higher education Syrian government, such as information about the Syrian public universities like the name of the university (Syrian Virtual University, Tishreen, Aleppo, Damascus, and Al Baath), address of the university, its web site, number of students and a summary of the university, which helps intelligent agents to find those services dynamically.